منهج القرآن في إدارة سلوك الإنسان السلبي: الإيذاء بالقول أنموذجا = The Quranic approach to confronting negative human behavior: verbal abuse as a case study - Almeri, Halah; Elatrash, Radwan Jamal Yousef (Karabük University, Turkiye, 2024)
يهدف هذا البحث إلى التعرف على بعض السلوكيات الإنسانية السلبية المؤذية على المستوى اللفظي وتقديم علاجات منهجية لها في ضوء القرآن الكريم، ذلك أن القرآن الكريم هو المقياس أو الأساس الذي يحكم به ويقوم السلوكيات والأفعال والأحكام في مختلف جوانب الحياة الإنسانية. كما يهدف هذا البحث إلى دعوة الأفراد وغيرهم من المؤسسات إلى الاستناد على التعاليم القرآنية كأساس للتقويم السلوكي، وذلك من أجل تحليل واستكشاف بعض السلوكيات اللفظية من خلال الاعتماد على تفسير علماء المسلمين للآيات القرآنية، وأيضًا النصوص الشرعية النبوية التي تناولت جانب السلوك الإنساني اللفظي. وكان المنطلق في هذه الدراسة الاعتماد على المنهج الاستقرائي، والمنهج التحليلي المقارن بين علم النفس الإسلامي وبين ما قاله علماء التفسير القرآني. وقد توصل البحث إلى بعض النتائج المهمة، منها: إن القرآن الكريم هو المعيار القويم الذي أثبتت خطاباته بتأكيد استعمال الكلام الطيب الحسن وتجنب استخدام الأذى اللفظي والفعلي وطالب المؤمنين على اختلاف مستوياتهم بالبعد عن الجدال واستخدام الألفاظ الجارحة، وكان في كثير من الأحيان يستخدم الكناية والتعريض ليتجنب استخدام التصريح بالألفاظ المؤذية شعورياً ونفسياً. كما طالب القرآن المؤمنين بالصبر والعفو وعد ذلك من عزم الأمور، ووصف عباد الرحمن بعدم الرد على الإساءة بالإساءة، بل طالبهم بمواجهة الإساءة بالأخلاق العالية والسلوكيات النظيفة والحسنة. ***** This research aims to identify the standardization of negative harmful human behaviors on both verbal and physical levels, and to present treatments for them in light of the Holy Quran, as the Quran is the measure or basis that governs and corrects behaviors, actions, and judgments in various aspects of human life. Additionally, this research aims to encourage individuals and institutions to base their behavioral assessments on Quranic teachings. This is done through analyzing and exploring some verbal and physical behaviors by utilizing guidance and assistance to present models of these behaviors and their treatments based on the interpretations of Muslim scholars of Quranic verses, as well as prophetic legal texts that dealt with the aspect of human behavior, serving as evidence and support for this approach. The starting point of this study was based on the inductive method and the comparative analytical approach between Islamic psychology and the interpretations of Quranic scholars. The research has reached some important conclusions, including: The Holy Quran is a correct standard whose discourses have confirmed the importance of using good speech and avoiding verbal and physical harm. It has urged believers at all levels to avoid arguments and the use of hurtful language, often using metaphor and implication to avoid outright harmful expressions emotionally and psychologically. The Quran has also called upon believers to practice patience and forgiveness, considering this to be from resolute matters, and has described the servants of the Merciful as not responding to harm with harm, but rather facing it with high morals and clean, good behaviors.